A catheterizable serous-lined urinary outlet associated with the ileal bladder augmentation Abol-Enein and Ghoneim procedure: a safe and reliable procedure in children - Alliot, Hortense; Tapsoba, Toussaint; Paye-Jaouen, Annabel; Ashkanani, Yaqoub; Josset-Raffet, Eliane; Natio, Lise; Peycelon, Matthieu; El-Ghoneimi, Alaa (Frontiers in Pediatrics, 2024)
Purpose This study aims to evaluate the long-term outcome of the serous-lined extramural continent catheterizable outlet procedure (SLECCOP) associated with ileal bladder augmentation in children. Methods This was a monocentric and retrospective study (2002–2021) that included children (<18 years) undergoing the SLECCOP associated with W-shaped ileocystoplasty with a catheterizable channel (Abol-Enein and Ghoneim procedure). Patients who received other types of bladder augmentation or W-shaped ileocystoplasty without a catheterizable channel were excluded. Patient records were reviewed for demographic information, surgical data, and long-term outcomes. Results This study included 52 children [33 boys, median age: 8.5 (0.8–18) years]. Pathological conditions included 28 children with the bladder exstrophy and epispadias complex (BEEC), 11 with neurogenic bladders, and 13 with other pathologies. Two patients underwent total bladder substitution. Thirty-four (65%) patients had bladder neck reconstruction (BNR), with 23 undergoing the SLECCOP and ileocystoplasty and 11 having prior BNR. All stomas, except for two, were umbilical, and were associated with omphaloplasty in 28 patients with the BEEC. A total of 40 stomas were created using the appendix (77%) and 12 with a Monti tube (23%). Stoma-related complications included cutaneous strictures (n = 2, 4%) and leaks (n = 10, 19%), all treated by dextranomer/hyaluronic acid copolymer injection (n = 10). A redo surgery was required in three patients: extraserosal wrapping was performed for persistent leakage (n = 2, 4%), and surgical revision was required for the Monti tube procedure (n = 1, 2%). Three patients (6%) underwent dilatation for transient stoma stenosis. Leakage occurred in 20% of appendix channels (n = 8/40) and 17% of Monti tubes (n = 2/12). Strictures were reported in 3% of appendix channels (n = 1/40) and 8% of Monti tubes (n = 1/12). Bladder stones developed in four patients (8%). Channel leakage persisted in one patient (2%) at a median follow-up of 4.4 years (IQR 1.4–9.7). Conclusion W-Ileal bladder augmentation with the SLECCOP is an efficient technique for treating children with incontinence caused by different etiologies. The rate of channel complication is very low, specifically for strictures, in this complex population of patients.